Overview of S-RBD Antibody Levels After Covid-19 Vaccination in Premenopausal and Menopausal Women - Saimin, Juminten; Irawaty, Irawaty; Purnamasari, Nur Indah; Purnamasari, Yenti; Asri Mulyawati, Sufiah (Indonesian Socety of Obstetrics and Gynecology, 2023)
Objective: To determine the levels of S-RBD antibodies in premenopausal and postmenopausal women who received the COVID-19 vaccine. Methods: This study involved 21 premenopausal and postmenopausal women who received two doses of CoronaVac at 28 days intervals. The duration of vaccination was 4-24 weeks. This study was conducted on May–October 2021 in Kendari City, Indonesia. Blood samples were taken at a health care facility and examined at the Prodia Clinical Laboratory. Participants were healthy women, willing to participate, and signed informed consent. Participants were excluded if they had a history of COVID-19, had taken antibiotics or immunomodulators in the last 24 hours, had a history of acute/chronic inflammatory disease and malignancy, were traumatized and received monoclonal antibody therapy. Results: Participants were 52.95±7.61 years old. The duration of the second vaccination was 13.67±5.26 weeks. The lowest level of S-RBD antibody was menopause with vaccination duration <=12 weeks (185.59±112.34 U/mL), and the highest was premenopause with vaccination duration >12 weeks (257.5±3.54 U/mL). The S-RBD antibody level in premenopausal women was higher than in menopausal women at the duration of vaccination <=12 weeks (223.37±63.45 vs 185.59±112.34 U/mL) and >12 weeks (257.5±3.54 vs. 225.55±91.14 U/mL). There was no significant difference in S-RBD antibody levels between two or more groups (p>0.05). Conclusion: S-RBD antibody levels in postmenopausal women after receiving two doses of COVID-19 vaccine were lower than in premenopausal women, but the difference was not significant. S-RBD antibody levels in postmenopausal women increased with increasing duration of vaccine administration. Keywords: menopause, immune response, COVID-19 vaccine, S-RBD antibody